Assessment of Frequency of Fast Food Consumption of DLSU-LC Grade 12 Students Using Food Delivery Apps - Hermosa, Mari-Len C. (Animo Repository, 2022)
The lockdowns implemented to prevent the spread of COVID-19 has increased the utilization of third-party food delivery services (FDS) in order to purchase food. However, the food available in these services are mostly fast-food. Frequent consumption of fast food is often associated with negative health outcomes. This study identified the relationship between the BMI and the frequency of using fast food delivery services of the participants who are in grade 12 students of De La Salle University Laguna Campus. The research conducted has used a quantitative-correlational approach study that gathered primary data through the use of a survey questionnaire. For the data analysis, linear regression analysis and multiple regression analysis were used with a 95% confidence level and an alpha of 0.05. The results of the analyses performed using the linear regression showed that there is a strong relationship between the consumption of fast food and the frequency of using FDS, however, results implied a weak correlation on the BMI of the students. Furthermore, the other factors also revealed to have no correlation with the frequency of using FDS which contradicts previous studies. Future studies similar to this could consider a bigger sample size and explore other locations to get a better understanding of the relationship between the factors.